Factors influencing MOW deinking : laboratory scale studies - Pala, H. (2006)
The deinking of MOW is examined at laboratorial scale. The effect of deinking aids, pre-washing and mixing are studied. The operating conditions during pulp treatment affect the pulp and paper properties, interfering with the mechanism of ink removal and modifying the ink particle characteristics. Pre-washing the pulp facilitates the deinking process. Cellulolytic enzymes and deinking chemicals are comparable in terms of ink removal ability.